1996
DOI: 10.1016/s0006-3495(96)79695-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of increasing membrane curvature on the phase transition and mixing behavior of a dimyristoyl-sn-glycero-3-phosphatidylcholine/ distearoyl-sn-glycero-3-phosphatidylcholine lipid mixture as studied by Fourier transform infrared spectroscopy and differential scanning calorimetry

Abstract: The phase transition behavior of a lipid bilayer of dimyristoyl-sn-glycero-3-phosphatidylcholine/distearoyl-sn-glycero-3- phosphatidylcholine (DMPC-d54/DSPC) (1:1) on a solid support with varying curvatures was investigated with differential scanning calorimetry, infrared spectroscopy, and model calculations. With increasing curvature the temperatures of the liquidus and solidus points are shifted to lower values by up to 7 degrees C and 15 degrees C, and the mixing of the two lipid species in the two phase re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 15 publications
6
66
0
1
Order By: Relevance
“…Figure 5 depicts a schematic overview of the lipid‐phase order for both nanodiscs and liposomes. We found that the response of lipid dynamics to a temperature change crossing T m deviates in nanodiscs (Figure 5 C and D) from the classical picture found in liposomes in this study (Figure 5 A and B) and that reported in the literature 6, 33. Specifically, we observed that DMPC molecules in liposomes were in the gel phase below 20 °C and adopted a tilted position with respect to the bilayer normal,26, 42 with very tight packing (Figure 5 A).…”
Section: Resultssupporting
confidence: 46%
“…Figure 5 depicts a schematic overview of the lipid‐phase order for both nanodiscs and liposomes. We found that the response of lipid dynamics to a temperature change crossing T m deviates in nanodiscs (Figure 5 C and D) from the classical picture found in liposomes in this study (Figure 5 A and B) and that reported in the literature 6, 33. Specifically, we observed that DMPC molecules in liposomes were in the gel phase below 20 °C and adopted a tilted position with respect to the bilayer normal,26, 42 with very tight packing (Figure 5 A).…”
Section: Resultssupporting
confidence: 46%
“…In contrast, molecular dynamics (MD) simulations pointed to an increasing diffusion coefficient with increasing vesicles size with the highest value for planar bilayers (7). Other properties, such as fusion rate (18, 23), phase transition temperature (19,24,25), and elasticity (20), have been shown to vary for vesicles of different sizes.NMR studies can provide a great deal of information on bilayer dynamics and order parameters. They have been used to investigate the effect of vesicle curvature on the dynamics of lipid acyl chains.…”
mentioning
confidence: 99%
“…Experimentally it has been found that the heat capacity profiles of the lipid melting process are broadened for curved membranes (10,29). This broadening reflects that the work necessary to bend the membrane is temperature dependent (Fig.…”
Section: Modeling the Transition Behavior Between Two Membrane Segmentsmentioning
confidence: 95%
“…This thermodynamic reasoning is quite general and does not depend on the details of the Monte-Carlo simulations that are used for this illustration. One may equally well use experimental heat capacity profiles for differently curved systems (10,29). Nor does it depend on specific characteristics of the morphological change, or the origin of the osmotic driving force.…”
Section: Modeling the Transition Behavior Between Two Membrane Segmentsmentioning
confidence: 99%